A comparative study on microwave-assisted catalytic transfer hydrogenation of levulinic acid to γ-valerolactone using Ru/C, Pt/C, and Pd/C. Issue 11 (2nd November 2021) - Hsiao, Chia-Yu; Chiu, Hsing-Yi; Lin, Tien-Yu; Lin, Kun-Yi Andrew
Abstract: Conversion of levulinic acid (LA) to γ-valerolactone (GVL) via catalytic transfer hydrogenation (CTH) using conventional heating (CH) involves long reaction times, and low yields. Microwave (MW) heating seems a solution to address these issues as MW accelerates reactions and enhances yields. In this study, three typical catalysts, Ru/C, Pt/C and Pd/C, are compared for LA conversion using MW heating. In comparison to CH processes, MW-assisted processes significantly enhance LA conversion to GVL with higher yields by Ru/C and Pt/C. While elevated temperatures and secondary alcohols are favorable for LA conversion by these catalysts, Ru/C appears as the most effective catalyst as it can reach LA conversion as 100%, selectivity of GVL as 99% and yield of GVL as 99% at 160 °C. The results of this study confirm that MW was a promising process for enhancing LA conversion and Ru/C shows the highest catalytic activity, followed by Pt/C and Pd/C.